STUDENTS' PERCEPTION TOWARD THE USE OF TED TALK VIDEO IN LEARNING VOCABULARY - Alma Hayati Muthmainnah; Eni Rosnija; Wardah (JEELL (Journal of English Education, Linguistics and Literature), 2025)
This research aims to determine students' perceptions of using TED Talks videos in learning vocabulary. This research is descriptive study, collected data by disturbing questionnaire to the Eight Semesters of the English Language Education Study Program, Faculty of Teacher Training and Education, Universitas Tanjungpura. Quantitative as research method and use questionnaire for tools of data collection. The questionnaire consists of five indicators, these indicators are categorized as perceived ease of use, usefulness, efficacy, compatibility and intention of use. Students show an excellent response in using TED Talks videos. This can be seen from the mean data the score shows medium category. Therefore, indicate that students positively view the ease of use of TED Talks Videos. Researchers found that students showed good responses and negative responses to TED Talks videos. Positive side regarding usefulness, efficacy, and compatibility. Meanwhile, the negative is related to they wanted more satisfaction with easy of use and intention of use.